Establishment of Autonomous and Non-Autonomous Pious Foundations: Canon 1304 - Abbass, Jobe J. (CLSA advisory opinions, 2001-2005, 2001)
Is particular law to define additional conditions for the establishment and acceptance of both autonomous and non-autonomous pious foundations?